Hybrid Desmoplastic/Follicular Ameloblastoma of the Mandible: A Case Report and Review of the Literature - Masayasu Iwase; Airi Fukuoka; Yoko Tanaka; Naoyuki Saida; Eriko Onaka; Sanae Bando; Gen Kondo (Case Reports in Pathology)
Desmoplastic ameloblastoma (DA) is one of the 6 histopathological subtypes of ameloblastoma. Hybrid lesions in which histopathologically conventional ameloblastoma coexists with areas of DA are rare. A 40-year-old male was referred to our hospital complaining of a swelling in the right premolar region of the mandible. A panoramic radiograph showed an area of radiolucency with a well-defined corticated border, whereas computed tomography revealed a unilocular radiolucent lesion and buccal expansion together with cortical perforation. The lesion was treated via enucleation and curettage of the marginal bone and fenestration. A histopathological examination showed a hybrid ameloblastoma with a pronounced desmoplastic pattern and follicular changes. The patient’s postoperative course has been favorable up to now, and no marked changes have been observed. We presented a case of hybrid ameloblastoma and reviewed the 36 reported cases of hybrid ameloblastoma that have been reported in the English literature.